Directionally assembled MoS2 with significantly expanded interlayer spacing: a superior anode material for high-rate lithium-ion batteries. (4th May 2018) - Wei, Qilin; Gao, Min-Rui; Li, Yan; Zhang, Dongtang; Wu, Siyu; Chen, Zonghai; Sun, Yugang
Abstract : Interlayer-expanded MoS2 nanosheets directionally assembled on multi-walled carbon nanotubes represent a new class of anode materials for lithium ion batteries with superior high rate capacity. Abstract : Despite the great promise of molybdenum disulfide (MoS2 ) as a storage anode for rechargeable lithium-ion batteries, the corresponding rate capacity is limited by the low electrical conductivity and kinetic barriers linked to ion diffusion, which prevents MoS2 from being used in current electrical energy storage devices. A feasible strategy is reported to tackle these challenges by directionally growing MoS2 nanosheets with an expanded interlayer spacing ( i.e., 9.4 Å versus 6.15 Å for pristine 2H-MoS2 ) on multiwalled carbon nanotubes (MWCNTs), which is performed through the microwave-assisted solvothermal reduction of ammonium tetrathiomolybdate [(NH4 )2 MoS4 ] in dimethylformamide in the presence of MWCNTs. The intimate interfaces between the MoS2 edges and the MWCNTs as well as the expanded interlayer gaps in MoS2 offer efficient and rapid pathways for ion and electron transport, which is favorable for improving the performance of batteries and enables the highest rate capability to be achieved. Batteries containing the as-synthesized MoS2 /MWCNT anodes can constantly deliver a reversible capacity of 390 mA h g −1 at a current rate of up to 57.312 A g −1 (36C), describing the first class of MoS2 -based anodes promising for high-rate use.